091 The East London Parkinson's disease project – engaging a diverse population in research. Issue 9 (12th August 2022) - Zirra, Alexandra; Ben-Joseph, Aaron; Haque, Tahrina; Gallagher, David; Budu, Caroline; Frances, Brooke; Simonet, Cristina; Noyce, Alastair
Abstract : Background: Parkinson disease (PD) is the second most common neurodegenerative disease and the burden appears to be growing fastest in middle-low and low income countries. In the majority of obser- vational studies of PD, White, well-educated and affluent participants are over-represented. Aims: Our aim was to engage a diverse group of people with Parkinson disease (PwP) from East London and build a research platform for previously under-represented groups. Methods: We created a register of PwP from the Royal London Hospital which includes approximately 400 patients. In parallel, we have recruited participants to the East London Parkinson's disease (ELPD) project; a case-control study of phenotype, genotype and biomarker characteristics. Clinical manifes- tations, UPDRS scores, data on non-motor symptoms, as well as biospecimens (buccal and skin swabs, serum samples) have been obtained. Results: 145 patients and 80 controls have been recruited so far. The mean age of PwP was 67.81 (SD 10.4); 62% were male and 59% identified as being from South Asian or Black ethnicity. The most common presenting symptom was tremor (55.9%), followed by gait impairment (16.6%). Conclusion: The ELPD project is a platform study for under-represented patients with PD which provides important opportunities for collaboration and research to improve health inequalities.